2011
DOI: 10.1055/s-0039-1698876
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bleaching Gels on Surface Roughness of Nanofilled Composite Resins

Abstract: Objectives:The aim of this study was to investigate the superficial texture of composite restorations after different bleaching protocols.Methods:Filtek Supreme (S), Filtek Z350 (F), and Grandio (G) were compared to Opallis (O) and Filtek Z250 (Z) (control microhybrid composites) and to bovine enamel using three different bleaching agents: 35% hydrogen peroxide Whiteness HP (WHP), 35% Whiteness HP MAXX (WMAXX) and 16% carbamide peroxide Whiteness Standard (WS). Six specimens from each composite were treated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
16

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 20 publications
4
50
0
16
Order By: Relevance
“…9,10 Degradation of chemical composite resin structure not only affected the decrease of surface hardness but also cause microleakage activity, surface roughness and colour stabilisation on the composite resin. [17][18][19][20] Ellias and Sajjan 17 stated that teeth whitening materials formed microleakage between the teeth surface attachment and composite resin restoration. Microleakage is one of the causes of secondary caries through the initial procedure of the penetration of saliva liquid contained bacteria in restoration borders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Degradation of chemical composite resin structure not only affected the decrease of surface hardness but also cause microleakage activity, surface roughness and colour stabilisation on the composite resin. [17][18][19][20] Ellias and Sajjan 17 stated that teeth whitening materials formed microleakage between the teeth surface attachment and composite resin restoration. Microleakage is one of the causes of secondary caries through the initial procedure of the penetration of saliva liquid contained bacteria in restoration borders.…”
Section: Resultsmentioning
confidence: 99%
“…This research was found that the effect of teeth whitening materials provided more impact on the roughness surface of composite restoration compared with the tooth enamel. 20 This condition happened due to the broken chain of matrix and filler caused by free radicals of peroxide, thus leads to microscopic cracks and modification surface hardness of composite resin restoration. Li et al 19 showed the period of teeth whitening materials application to composite resin restoration impact in increasing free radical of peroxide and increased the broken chain of matrix and filler and finally altered the surface roughness of composite resin restoration.…”
Section: Discussionmentioning
confidence: 99%
“…26,38 This divergence of results can be explained by the presence of different components in both the organic and the inorganic matrix of composite resins; thus, even materials of the same classification can react differently to a bleaching agent. 39 Better mechanical properties of the adhesive interface can be related to better adhesion stability and longevity of restorations. [40][41][42] However, the adhesive interface is the most susceptible to degradation, and its exposure to bleaching agents may affect the longevity of the restoration.…”
Section: Discussionmentioning
confidence: 99%
“…When composite resins are submitted to bleaching agents, this chemical reaction may alter the surface characteristics (Hafez et al ., ; Rattacaso et al ., ) by accelerating the hydrolytic degradation (Wang et al ., ) and inducing oxidative cleavage of polymer chains in resin matrix (Hannig et al ., ). The degree of alterations can vary according to the composition, exposure procedure of bleaching gel and the content of resin material.…”
Section: Introductionmentioning
confidence: 99%